2019
DOI: 10.1002/prca.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigens in Chronic Obstructive Pulmonary Disease and Lung Cancer: A Point of View

Abstract: The goal of this manuscript is to explore the role of clinical proteomics for detecting mutations in chronic obstructive pulmonary disease (COPD) and lung cancer by mass spectrometry‐based technology. COPD and lung cancer caused by smoke inhalation are most likely linked by challenging the immune system via partly shared pathways. Genome‐wide association studies have identified several single nucleotide polymorphisms which predispose an increased susceptibility to COPD and lung cancer. In lung cancer, this lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…We and others previously showed that mutations in proteins in both cell cultures and tissues could be detected by mass spectrometry, including the IDH1 mutation, but for these measurements, an enrichment by immunoprecipitation of the mutated protein was required. 21,22 In the current study, we show that using the newest-generation mass spectrometry equipment, this step can be omitted. Using this assay, the IDH1 mutation could be confirmed in all IDH1 mut cultures and most of the tissues.…”
Section: ■ Discussionmentioning
confidence: 75%
“…We and others previously showed that mutations in proteins in both cell cultures and tissues could be detected by mass spectrometry, including the IDH1 mutation, but for these measurements, an enrichment by immunoprecipitation of the mutated protein was required. 21,22 In the current study, we show that using the newest-generation mass spectrometry equipment, this step can be omitted. Using this assay, the IDH1 mutation could be confirmed in all IDH1 mut cultures and most of the tissues.…”
Section: ■ Discussionmentioning
confidence: 75%
“…TP53 is one of the most well-known tumour suppressor and exerts multi-functional roles in controlling cell cycle checkpoints, apoptosis and DNA repair ( 40 ). In smokers with COPD, down-regulation of TP53 and p53-related signaling transduction may lead to lung tumorigenesis ( 41 ). Thus, these genes are reasonable as core targets for chenpi preventing COPD and its progression to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of the products of apoptosis cause reduced phagocytic capacities of macrophages and production of suppressory cytokines, among others TGFβ [ 37 ]. Thus, emphysema seems to be not only structural, but also immune disease [ 58 , 59 ].…”
Section: Pathogenesis and Common Pathwaysmentioning
confidence: 99%